Case Report: Intoxication in a Pig (Sus Scrofa Domesticus) After Transdermal Fentanyl Patch Ingestion - Sredenšek, Jerneja; Bošnjak, Maša; Lampreht Tratar, Urša; Kosjek, Tina; Cemazar, Maja; Kržan, Mojca; Seliškar, Alenka (Frontiers in Veterinary Science, 2020)
An experimental study on the effects of electroporation on pancreatic tissue was performed in pigs, and the fentanyl transdermal patch (FTP) was used postoperatively as part of multimodal pain management. Ingestion of an FTP, which resulted in fentanyl intoxication, was suspected five days after placement in one of the experimental pigs. The pig was first dysphoric, running in the stall, panting and vocalizing until it finally became depressed and it remained lying on the floor. Ingestion of an FTP was not observed but the fentanyl plasma concentration on the day of intoxication was 20.7 ng/ml, while at its peak after FTP administration it was only 0.492 ng/ml. The intoxication was successfully treated with a single intramuscular naloxone injection.